Pengaruh Variasi Serat Fiberglass Terhadap Kekuatan Tarik Komposit High Density Polyethylene - Jhenris Ivanly; M Dalil; Dodi Sofyan Arif (Proksima, 2023)
This research was aimed to determine the effect of fiberglass fibers in increasing the tensile strength of HDPE composites and their advantages over PVC materials. The specimens were printed using a hot press by pressing and heating at a temperature of 140°C, mixing the materials was carried out by mixing in a measuring cup, then cutting was carried out for tensile testing with the ASTM D3039 standard on the specimen. The results of the study obtained tensile strength with a fraction of 70% vol HDPE resin, 30% vol fiber fiberglass average of 13.774 Mpa with short fiber type and fraction 75% vol HDPE resin, 25% vol fiber fiberglass average of 24,334 Mpa for this type of fiber the length and tensile strength of PVC material has a value of 7 25 Mpa, the tensile strength of HDPE fiberglass composite of 24,334 Mpa is sufficient to replace PVC.